Therapeutic expansion of JAK inhibitors in Chinese dermatological practice: beyond atopic dermatitis to novel autoimmune frontiers - Xinyan Lyu; Yixi Wang; Jingyi Yang; Yiwen Zhang; Wei Min; Na Du (Frontiers in Medicine, 2026)
Janus kinase inhibitors (JAKi) have demonstrated clinical utility in managing atopic dermatitis (AD), yet their broader potential across immune-mediated dermatoses remains inadequately explored, particularly within China’s restrictive regulatory landscape for dermatologic indications. This review examines pathogenic mechanisms and emerging evidence supporting JAKi repositioning in seven dermatological conditions beyond AD: alopecia areata (AA), vitiligo, psoriasis, dermatomyositis (DM), pemphigus, bullous pemphigoid (BP), and chronic spontaneous urticaria (CSU)—with emphasis on therapeutic gaps and opportunities specific to Chinese practice. We delineate disease-specific JAK-STAT dysregulation, including IFN-γ-driven cytotoxicity in AA/vitiligo, IL-23/STAT3 activation in psoriasis, and type I interferon hyperactivation in DM. Key clinical findings from rigorous trials indicate that oral tofacitinib achieves PASI75 in 58% of psoriatic patients within 16 weeks and topical ruxolitinib induces facial repigmentation exceeding 75% in vitiligo. In contrast, while current evidence is substantially limited to isolated case reports, emerging data suggest that baricitinib may resolve steroid-refractory BP lesions within one month. Persistent limitations include reliance on small-scale studies for pemphigus and CSU, along with unresolved safety concerns regarding thrombosis risks in susceptible populations. Crucially, we identify therapeutic gaps in segmental vitiligo and juvenile DM where clinical data are absent. This synthesis advocates for randomized controlled trials to validate JAKi efficacy against biologics in high-burden diseases currently dependent on glucocorticoids.